Exclusion from school and recognition of difference. Issue 4 (3rd July 2016) - McCluskey, Gillean; Riddell, Sheila; Weedon, Elisabet; Fordyce, Mariela
ABSTRACT: There has been an overall decrease in exclusion rates and numbers in recent years across the UK. This change has often been heralded as evidence that national inclusion policies are 'working' and that schools themselves are becoming increasingly inclusive. This article examines findings from a recent study on school exclusion in Wales, noting that exclusion is falling here in line with UK wide trends. However, exclusion rates of children with special needs and others who face multiple disadvantages remain stubbornly high. Given these findings, and the evidence that this is the case across the UK, an important question arises about the broader relationship between school exclusion and inequality. This article seeks to address this question, and asks whether and to what extent the politics of recognition of difference, in Nancy Fraser's terms, can help explain the continuing over-representation of some groups of marginalised and vulnerable children in exclusion figures, despite this overall downward trend.